Strategi Mobile Seamless Laerning dan Literasi Digital terhadap Penguasaan Konsep Siswa pada Mata Pelajaran PAI - Destatil Maghfiroh; Nurul Faizah; Nur Aisyah (AFKARINA: Jurnal Pendidikan Agama Islam, 2021)
The growing development of science accompanied by the emergence of social, cultural, and economic growth is evidence that technology and information in Indonesia are starting to grow in a positive direction. The disconnection of formal education and non-formal education makes educators out of sync and makes it difficult for students to master learning concepts, limited hours in class require a solution. The Mobile Seamless Learning Strategy is promoted to be able to accommodate the achievement of students' mastery of concepts. This strategy connects education at school and outside of school, using digital media. Another factor to consider is digital literacy. The method used to collect data is the literature study method, by collecting relevant data from books, journals, dictionaries, magazines, and so on without having to conduct field research. With this research, students can master the concept of students in understanding learning material. So as to achieve the target to be achieved.